Implementing Sustainable HR Practices: A New Paradigm in Building Organizational Capacity to Address the Climate Crisis - Wiyono, Darul; Setiadi, Hedi; Tanjung, Rinaldi; Julaeha, Ela; Ambarsari, Megie (Integrated Journal of Business and Economics (IJBE), 2025)
This study examines the implementation of sustainable Human Resource (HR) practices and their impact on organizational capacity to address climate crises in private universities in Bandung City. The research background highlights the importance of integrating sustainability principles into HR policies to strengthen organizational resilience against global environmental challenges. This study aims to analyze the influence of sustainable HR practices on organizational culture, managerial support, and climate resilience within higher education institutions. A quantitative research method was employed, utilizing the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to examine the relationships among key variables. The study involved a population of 882 individuals from 138 private universities in Bandung, with a representative sample of 270 participants determined using Slovin’s formula with a 5% margin of error and selected through stratified random sampling. The sample was proportionally distributed across university management (rectors, vice rectors, and department heads), lecturers, and administrative staff to ensure comprehensive representation of the population. The results indicate that sustainable HR practices significantly influence organizational culture and managerial support, which subsequently enhance organizational resilience to climate crises. The study concludes that integrating sustainable HR practices into the policies of private universities can improve institutional capacity to address climate change. Practical implications include the development of holistic sustainability policies and increased managerial engagement to effectively support sustainability implementation.